If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + -38 = -6(-3 + -5x) + 8 Reorder the terms: -38 + -2x = -6(-3 + -5x) + 8 -38 + -2x = (-3 * -6 + -5x * -6) + 8 -38 + -2x = (18 + 30x) + 8 Reorder the terms: -38 + -2x = 18 + 8 + 30x Combine like terms: 18 + 8 = 26 -38 + -2x = 26 + 30x Solving -38 + -2x = 26 + 30x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30x' to each side of the equation. -38 + -2x + -30x = 26 + 30x + -30x Combine like terms: -2x + -30x = -32x -38 + -32x = 26 + 30x + -30x Combine like terms: 30x + -30x = 0 -38 + -32x = 26 + 0 -38 + -32x = 26 Add '38' to each side of the equation. -38 + 38 + -32x = 26 + 38 Combine like terms: -38 + 38 = 0 0 + -32x = 26 + 38 -32x = 26 + 38 Combine like terms: 26 + 38 = 64 -32x = 64 Divide each side by '-32'. x = -2 Simplifying x = -2
| 3x^2+5x-2=12 | | 5x^2-20x-20=0 | | y+(x*x)=5 | | 8x-28=-2x+12 | | 5x^2-20-20=0 | | y=h*h | | =(x-1)(x^2+5x-6) | | -7x-6=2+3x | | y=6h*h | | x^4-52500x^2+1250000=0 | | -(3x+9)=24 | | 12.36=S-6.63 | | 3x-12(3x)=0.25 | | 10x+3y+5=0 | | 6y+3=-y+31 | | 2.5n=18.5 | | 2g-3.1=1.7 | | -5x-7=6x+5(4-8x) | | 6y-2x+1= | | -18m-24=-6+48 | | 11-3x=-4x | | 7x+3=4x+3 | | 4d+9=7d | | 5b+7-12b-29= | | 4n+1=5n+20 | | 14n-6-5n-29= | | 3[x-4]=8[x-9] | | 10x+3x+8x= | | 5times=135 | | (x-1)(x^2+5x-6)= | | (6x+6)+(10x-30)= | | 2x^2-6x=80 |